Fibre grating refractometer sensors for composite process monitoring - Buggy, Stephen J.; Chehura, Edmon; Skordos, Alexandros A.; Dimopoulos, A.; James, Stephen W.; Partridge, Ivana K.; Tatam, Ralph P. (Cranfield University, 2007)
Optimum performance from advanced composites requires careful control of the resin matrix during cure. This is to ensure there are no cure induced voids and to minimise the build up of internal stresses. Careful control of the process is also necessary to reduce wastage. Traditional resin inspection techniques are bulk or sample oriented and thus cannot provide data about critical component parts. Optical fibre based sensors however, allow for in-situ monitoring techniques to be deployed in components without effecting their structural integrity. In this work, two fibre optic grating techniques are demonstrated as process monitoring sensors and are compared with a Fresnel refractometric method. The change in refractive index of a resin has previously been used as a means for assessing the degree of cure. The central wavelength of an attenuation band of a long period grating (LPG) was monitored during the cure of a resin. In parallel the spectral resonances of a tilted fibre Bragg grating (FBG) are also monitored. The two techniques are shown to correlate well with the Fresnel based method in both detecting the resin and monitoring the state of cure, indicating the potential of the techniques for online production monitoring